(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
Contrary to popular belief, sciences and humanities are not contrary to each other; in fact, they are complementary in terms of human development as a process of constant progress. Day by day, scientific progress opens technological horizons where the humanities can find nesting spaces.